Interpersonal Competence, Entrepreneurial Characteristics as Market Orientation Basis and Micro and Small Enterprises in Start-up Business Phase - Abraham, Fenri; Tupamahu, Stevi (Universitas Brawijaya, Indonesia, 2016)
This study aims to examine the effect of direct and indirect influence interpersonal competence, entrepreneurial characteristics towards market orientation and business performance of micro and small enterprises in the start-up phase of business. This research is a study explanatory, the unit of analysis is the micro and small enterprises in the start-up phase of a business in the city of Ambon. The samples using non-probability sampling methods (purposive sampling), the selection of the sample in this study using sampling techniques judgment sampling, the number of samples in the study as many as 128 units. Data analysis using inferential statistical tool that is Path Analysis. The results of the study explains that entrepreneurs interpersonal competence affect market orientation, entrepreneurial characteristics affecting the market orientation. Interpersonal competence entrepreneurs directly affect business performance. Entrepreneurial characteristics directly influence business performance. Market orientation affects the performance of small businesses and micro-enterprises that are in the start-up phase of business. Market orientation proved to mediate the effects of interpersonal competence and entrepreneurial characteristics on the performance of small businesses and micro-enterprises that are in the start-up phase of a business in the city of Ambon.